Pre-modern towns at the times of catastrophes East Central Europe in a comparative perspective - Antonín Malaníková, Michaela; Możejko, Beata ca. 20./21. Jh; Nodl, Martin 1968- (Routledge, 2024)
"Covering areas in today's Ukraine, Poland, Bohemia, Moravia, Silesia and Slovakia, this book studies the impact of both natural and human-inflicted disasters on pre-modern towns. This volume is an engaging resource for students and researchers of pre-modern history, social history and disaster studies"--